Explaining the Prevalence of the Informal Economy in the Baltics: an Institutional Asymmetry Perspective - Williams, Colin C.; Horodnic, Ioana A. (European Spatial Research and Policy, 2015)
Reporting a 2013 Eurobarometer survey of participation in the informal economy across eight Baltic countries, this paper tentatively explains the informal economy from an institutional perspective as associated with the asymmetry between the codified laws and regulations of the formal institutions (state morality) and the norms, values and beliefs of citizens (civic morality). Identifying that this non-alignment of civic morality with the formal rules is more acute when there is greater poverty and inequality, less effective redistribution and lower levels of state intervention in the labour market and welfare, the implications for theorising and tackling the informal economy are then discussed.